An Innovative Low-Power, Low-Cost, Multi-Constellation Geodetic-Grade Global Navigation Satellite System Reference Station for the Densification of Permanent Networks: The GREAT Project - Davide Curone; Giovanni Savarese; Mirko Antonini; Raphaël Baucry; Elie Amani; Antonin Boulandet; Marco Cataldo; Paul Chambon; Massimiliano Chersich; Ahmed B. Hussein; Bruno Menuel; Avag Tsaturyan (Sensors, 2023)
Geodetic-grade Global Navigation Satellite System (GNSS) receivers designed to implement permanent stations represent the most complex and costly technology in the field of GNSS instrumentation. On the other hand, a large number of innovative applications, highly demanding in terms of positioning precision and accuracy, is pushing the implementation of networks of permanent stations with a higher and higher spatial density. In this scenario, the development of brand new GNSS reference stations, which combine the most advanced technologies in the field of data availability and integrity together with reduced costs (of instrumentation, installation and management) is becoming of paramount importance. For this reason, in 2019 the EU Agency for the Space Programme (EUSPA) has financed a research project, called “next Generation gnss REference stATion—GREAT”, aimed at developing and demonstrating the potentiality of a brand new GNSS receiver suitable to implement permanent stations. This paper describes the solution developed by the project consortium, composed of four Small or Medium Enterprises (SMEs) based in Italy, France and Belgium, and the preliminary results achieved in the field tests.